Brahman Genetics Negatively Impact Protein Degradation and Tenderness of Longissimus Lumborum Steaks, but do Not Influence Collagen Cross-Linking - K. J. Phelps; D. D. Johnson; M. A. Elzo; C. B. Paulk; J. M. Gonzalez (Kansas Agricultural Experiment Station Research Reports, 2017)
Beef tenderness is an important factor contributing to consumer eating satisfaction of beef products. Tenderness is dependent on several factors including: breed-type, postmortem age time, myofibrillar muscle protein degradation, and collagen content. During the past 30 years, numerous studies have indicated steaks from cattle with a greater percentage of Brahman genetics are tougher than steaks from Bos taurus cattle. The cause of tougher steaks is commonly attributed to Brahman cattle having a greater calpastatin activity which inhibits calpains, the enzymes responsible for myofibrillar protein degradation during the postmortem aging process. Some researchers have reported calpastatin activity was poorly correlated to tenderness of steaks from Brahman cattle. Others have reported sensory panelists indicated steaks from cattle with increasing percentages of Brahman genetics have an increase in the amount of connective tissue or collagen. Additionally, researchers have reported an increase in expression of genes that play a role in cross-linking of collagen which decreases collagen solubility. Due to these findings, we hypothesized steaks from cattle with greater Brahman genetics have more collagen cross-links and therefore a less soluble collagen fraction. The objective of this study was to evaluate the effect of Brahman genetics on protein degradation, collagen cross-linking, and meat tenderness of strip loin steaks.
Keywords: Brahman; collagen; tenderness